2015
DOI: 10.1086/679576
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Test of the Maximum Entropy Theory of Ecology

Abstract: The maximum entropy theory of ecology (METE) is a unified theory of biodiversity that predicts a large number of macroecological patterns using information on only species richness, total abundance, and total metabolic rate of the community. We evaluated four major predictions of METE simultaneously at an unprecedented scale using data from 60 globally distributed forest communities including more than 300,000 individuals and nearly 2,000 species.METE successfully captured 96% and 89% of the variation in the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(103 citation statements)
references
References 66 publications
(68 reference statements)
4
96
1
Order By: Relevance
“…In spite of this, the IED remains a largely 344 successful metric because it is free of this particular problem. These results are consistent with 345 an independent study of tree communities (Xiao et al 2013), suggesting that the observed 346 relationships between the theoretical predictions and empirical data may be general, at least 347 within plants. it appears that the SED is exponential in form, the exponent itself (  2 n ) is a likely cause of the 365 highly regular pattern in mismatch between theory and data.…”
Section: Discussion 281supporting
confidence: 77%
“…In spite of this, the IED remains a largely 344 successful metric because it is free of this particular problem. These results are consistent with 345 an independent study of tree communities (Xiao et al 2013), suggesting that the observed 346 relationships between the theoretical predictions and empirical data may be general, at least 347 within plants. it appears that the SED is exponential in form, the exponent itself (  2 n ) is a likely cause of the 365 highly regular pattern in mismatch between theory and data.…”
Section: Discussion 281supporting
confidence: 77%
“…Regardless of the underlying reason that the models performed similarly, our results indicate that the SAD usually does not contain sufficient information to distinguish among the possible statistical processes—let alone biological processes—with any degree of certainty (Volkov et al, 2005), though it is possible that this result differs in marine systems (see Connolly et al, 2014). A more promising way to draw inferences about ecological processes is to evaluate each model’s ability to simultaneously explain multiple macroecological patterns, rather than relying on a single pattern like the SAD (McGill, 2003; McGill, Maurer & Weiser, 2006; Newman et al, 2014; Xiao, McGlinn & White, 2015). It has also been suggested that examining second-order effects, such as the scale-dependence of macroecological patterns (Blonder et al, 2014) or how the parameters of the distribution change across gradients (Mac Nally et al, 2014), can provide better inference about process from these kinds of pattern.…”
Section: Discussionmentioning
confidence: 99%
“…; Xiao et al . ). Our model successfully captures several aspects of coral reef metacommunity structure, even though it, like unified theories, predicts a broad range of ecological patterns with few free parameters (two for the regional species‐abundance distribution, and two power‐law scaling parameters for aggregation).…”
Section: Discussionmentioning
confidence: 97%
“…; Xiao et al . ). In addition, when tested against individual patterns, alternative models often make very similar predictions (for instance, truncated lognormal abundance distributions strongly resemble log‐series distributions); in such cases, the model with fewer parameters may well be favoured even if more comprehensive sampling, or testing against multiple patterns, would yield a different result.…”
Section: Introductionmentioning
confidence: 97%